Effect of Scouting Extracurricular Toward Character Values of Students at SDN Gedanganak 01 District East Ungaran, Semarang regency - Satrio Wicaksono, M.Pd; Sitepu, Melyani Sari; Sitepu, Juli Maini (Tadulako Social Science and Humaniora Journal, 2021)
This research is motivated by the problems of the low value of the student's character on SDN Gedanganak 01, which does not use attributes complete when the flag ceremony, taking out the trash is not in place, students who do not do their homework. The formulation of the problem is whether scouting extracurricular effect on the character values ​​of elementary school students. This study aims to determine the effect of scouting extracurricular on the character values ​​of student at SDN Gedanganak 01, District East Ungaran. The method used is quantitative. The study population were students of class IV and class V SD Negeri Gedanganak 01 with total 51 students. Data collection techniques in this study was the observation. Research hypothesis testing using t test. The results showed Scouting extracurricular effect on the character value of students at SDN Gedanganak 01. This is evidenced by the results of the analysis of the t-test is equal to 0.000 as significant value. The significant value of 0.000 ≤ α (0.05). So the hypothesis which says scouting extracurricular affect to character value of students at SDN Gedanganak 01, District East Ungaran accepted